Expert System for Diagnosing Cow Disease Using Web-Based Forward Chaining Method - Mohammad Rizal Ma'ruf; Ade Eviyanti (Procedia of Engineering and Life Science, 2022)
Media Technology and Information is currently developing quite quickly and well. Some people and even almost all of the surrounding community are familiar with technology, especially in the science of artificial intelligence. With this expert system, it can help alleviate the need when it is difficult to meet experts, especially livestock specialist diseases. The purpose and benefits of this expert system is to make it easier for researchers to identify livestock disease problems based on the symptoms suffered by cattle. The identification method used in this system is the Forward Chaining Method and collects symptom data from several sources and verified journals. The desired result of this research is the reduction of disease or outbreaks that occur in Livestock Cattle and provide prevention and treatment solutions so as not to be attacked by diseases and outbreaks..